Maternal knowledge related to anemia during pregnancy among a sample of mothers attending Primary Health Care centers. Baghdad. - Thabit, Maral F (AL-Kindy College Medical Journal, 2019)
Background: Anaemia is a major public health concern and is one of the most prevalent health issue in women within reproductive age group. Objective: to assess maternal knowledge related to anaemia during pregnancy. Type of the study: A cross –sectional study. Method: The study including 200 mothers who attended selected primary health care centres, Baghdad during November and December 2015, they completed a previously prepared questionnaire coveringsocio-demographic characteristics and knowledge regarding anaemia in 4 main domains. The responses were analysed by using frequency, percentage and percent score for each statement and overall percent score for each domain and mean overallpercent score for all the four domains. Results: the main source of information of the participated mothers was health personal (59.5%).The overall percent score for the main domains was good 71% for aetiology of disease, excellent 91% for signs and symptoms of anaemia, good 75% for complications of anaemia and very good 75% regarding ways of prevention and treatment. Conclusion: Satisfactory knowledge level of mothers regarding anaemia during pregnancy.